Chemo metric assisted Spectrophotometric Method Development through Quality by design Approach for the estimation of Bilastine and Montelukast sodium in combined solid dosage form - Bhagyashri D Kolekar,; Namrata N Gawade,; G K Dyade,; Nilesh Y Jadhav, (Indian Journal of Pharmacy & Drug Studies, 2024)
Objective: Quality by design (QbD) is a systematic process for pharmaceutical development recommended by regulatory agencies like USFDA. Development of various pharmaceutical processes including analytical methods by applying Quality by design aids in ensuring the robustness of the method. QbD approached chemo metric assisted UV-VIS spectrophotometric analytical method was developed for the estimation of Bilastine (BSE) and Montelukast sodium (MKS) from their combined dosage forms. Materials and Method: Simultaneous equation method was selected from the nature of spectra, solvent 50 % alcohol was utilised; and for method 274.5 nm and 351.5 nm was the wavelength for measurement of absorbance of bilastine and montelukast sodium respectively. Effect of input variables on spectrum characteristics were studied for selection of critical parameters and developed method was validated as per ICH Q 2 R1 regulatory guidelines. Linearity of the drugs was ascertained over the conc range 1-32 mcg/ml (microgram/ml) for BSE and 1-20 mcg/ml for MKS. Results and Discussion: The percentage purity of assay was found 98.09 % for BSE and 103.62 % for MKS; and the accuracy study data were varied from 0.2523 to 0.5221 for BSE and 0.2512 to 1.2515 for MKS. Precision study was shown acceptable data as SD data varied from 0.1902 to 0.5773 for BSE and from 0.2828 to 0.5458 for MKS. Conclusion: The developed method is rigid, robust and efficient for the estimation of BSE and MKS from the composition of dosage form. QbD was applied to build rigid robust method through risk assessment at early stage and defining the design space at the later stage.